External validation of the Systemic Lupus International Collaborating Clinics Frailty Index as a predictor of adverse health outcomes in systemic lupus erythematosus. (19th August 2021) - Legge, Alexandra; Malone, Alicia; Hanly, John G
Abstract: Objective: The SLICC frailty index (SLICC-FI) was recently developed as a measure of susceptibility to adverse outcomes in SLE. We aimed to externally validate the SLICC-FI in a prevalent cohort of individuals with more long-standing SLE. Methods: This secondary analysis included data from a single-centre prospective cohort of adult patients with established SLE (disease duration >15 months at enrolment). The baseline visit was the first at which both SLICC/ACR Damage Index (SDI) and 36-item Short Form data were available. Baseline SLICC-FI scores were calculated. Cox regression models estimated the association between baseline SLICC-FI values and mortality risk. Negative binomial regression models estimated the association of baseline SLICC-FI scores with the rate of change in SDI scores during follow-up. Results: The 183 eligible SLE patients were mostly female (89%) with a mean age of 45.2 years (s .d . 13.2) and a median disease duration of 12.4 years (interquartile range 7.8–17.4) at baseline. The mean baseline SLICC-FI score was 0.17 (s .d . 0.09), with 54 patients (29.5%) classified as frail (SLICC-FI >0.21). Higher baseline SLICC-FI values (per 0.05 increase) were associated with an increased mortality risk [hazard ratio 1.31 (95% CI 1.01, 1.70)] after adjusting for age, sex, education, SLE medication use, disease duration, smoking status and baseline SDI. Higher baseline SLICC-FI values (per 0.05 increase) were associated with increased damage accrual over time [incidence rate ratio 1.18 (95% CI 1.07, 1.29)] after adjusting for potential confounders. Conclusion: Frailty, measured using the SLICC-FI, predicts organ damage accrual and mortality risk among individuals with established SLE.